Chick Lit authorship and the twenty-first century zeitgeist - Abu Ujum, Diana; Talif, Rosli; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2017)
This paper attempts to establish that the zeitgeist emerges from trends of the times and imprinted onto Chick Lit, a genre of popular postfeminist fiction, through authorship from the point of Chick Lit’s emergence to its rise in popular culture. This paper traces the origins of Chick Lit to better pinpoint the current trends or spirit of the times that serve as the backdrop or cultural landscape Chick Lit writers have utilised. It demonstrates the contemporaneous nature of writers who produce the same kind of fiction around the same time from different parts of the world. The writers are exposed to prevalent popular culture throughout their lives that may influence their writing style and content. The qualitative method of this study detects these patterns based on data of Chick Lit writers’ real life experiences and documented trends from the early twenty-first century.